Tìm x:
( x2+8x+12 )( x2-7x+12 ) = 16x2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(3x^2+4x=2x\Leftrightarrow3x^2+2x=0\Leftrightarrow x\left(3x+2\right)=0\Leftrightarrow x=-\dfrac{2}{3};x=0\)
b, \(25x^2-\dfrac{64}{100}=0\Leftrightarrow25x^2-\left(\dfrac{8}{10}\right)^2=0\Leftrightarrow\left(5x-\dfrac{8}{10}\right)\left(5x+\dfrac{8}{10}\right)=0\)
\(\Leftrightarrow x=\dfrac{4}{25};x=-\dfrac{4}{25}\)
c, \(x^4-16x^2=0\Leftrightarrow x^2\left(x-4\right)\left(x+4\right)=0\Leftrightarrow x=0;x=-4;x=4\)
sửa d, \(x^2+x=6\Leftrightarrow x^2+x-6=0\Leftrightarrow\left(x-2\right)\left(x+3\right)=0\Leftrightarrow x=-3;x=2\)
e, \(x^2-7x=-12\Leftrightarrow x^2-7x+12=0\Leftrightarrow\left(x-4\right)\left(x-3\right)=0\Leftrightarrow x=3;x=4\)
e: ta có: \(x^2-7x=-12\)
\(\Leftrightarrow x^2-7x+12=0\)
\(\Leftrightarrow\left(x-3\right)\left(x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=4\end{matrix}\right.\)
a: \(=5x\left(xy^2+3x+6y^2\right)\)
b: \(=\left(x-2\right)\left(x+3\right)-\left(x-2\right)\left(x+2\right)=\left(x-2\right)\left(x+3-x-2\right)=\left(x-2\right)\)
c: \(=\left(x-3\right)\left(x-4\right)\)
d: \(=x\left(x^2-2xy+y^2-9\right)\)
=x(x-y-3)(x-y+3)
e: \(=\left(x+y\right)^2-25=\left(x+y+5\right)\left(x+y-5\right)\)
f: \(=\left(x-4\right)\left(x+3\right)\)
`a)16x^2-24x+9=25`
`<=>(4x-3)^2=25`
`+)4x-3=5`
`<=>4x=8<=>x=2`
`+)4x-3=-5`
`<=>4x=-2`
`<=>x=-1/2`
`b)x^2+10x+9=0`
`<=>x^2+x+9x+9=0`
`<=>x(x+1)+9(x+1)=0`
`<=>(x+1)(x+9)=0`
`<=>` \(\left[ \begin{array}{l}x=-9\\x=-1\end{array} \right.\)
`c)x^2-4x-12=0`
`<=>x^2+2x-6x-12=0`
`<=>x(x+2)-6(x+2)=0`
`<=>(x+2)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=-2\\x=6\end{array} \right.\)
`d)x^2-5x-6=0`
`<=>x^2+x-6x-6=0`
`<=>x(x+1)-6(x+1)=0`
`<=>(x+1)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=6\\x=-1\end{array} \right.\)
`e)4x^2-3x-1=0`
`<=>4x^2-4x+x-1=0`
`<=>4x(x-1)+(x-1)=0`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-\dfrac14\end{array} \right.\)
`f)x^4+4x^2-5=0`
`<=>x^4-x^2+5x^2-5=0`
`<=>x^2(x^2-1)+5(x^2-1)=0`
`<=>(x^2-1)(x^2+5)=0`
Vì `x^2+5>=5>0`
`=>x^2-1=0<=>x^2=1`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-1\end{array} \right.\)
\(1,A⋮B\Leftrightarrow x^3-3x^2-ax+3=\left(x-1\right)\cdot a\left(x\right)\)
Thay \(x=1\)
\(\Leftrightarrow1-3-a+3=0\\ \Leftrightarrow a=1\)
\(2,A⋮B\Leftrightarrow3x^3-16x^2+25x+a=\left(x^2-4x+3\right)\cdot b\left(x\right)\\ \Leftrightarrow3x^3-16x^2+25x+a=\left(x-3\right)\left(x-1\right)\cdot b\left(x\right)\)
Thay \(x=1\)
\(\Leftrightarrow3-16+25+a=0\\ \Leftrightarrow a=-12\)
Thay \(x=3\)
\(\Leftrightarrow3\cdot27-16\cdot9+25\cdot3+a=0\\ \Leftrightarrow81-144+75+a=0\\ \Leftrightarrow12+a=0\Leftrightarrow a=-12\)
Vậy \(a=-12\)
a, 7x - 14
= 7(x-2)
b, 2x - 2y + \(x^2\)- xy
= (2x-2y) + (\(x^2\)-xy)
= 2(x-y) + x(x-y)
= (x-y)(2+x)
c, 6x + 12
= 6(x+2)
\(a,=7\left(x-2\right)\\ b,=2\left(x-y\right)+x\left(x-y\right)=\left(x+2\right)\left(x-y\right)\\ c,=6\left(x+2\right)\\ d,\text{Sai đề}\)
\(\left(x-3\right)\left(4-x\right)>0\)
\(\Rightarrow\)\(\hept{\begin{cases}x-3>0\\4-x>0\end{cases}}\)\(\Leftrightarrow\)\(\hept{\begin{cases}x>3\\x< 4\end{cases}}\) (vô lí)
hoặc \(\hept{\begin{cases}x-3< 0\\4-x< 0\end{cases}}\)\(\Leftrightarrow\)\(\hept{\begin{cases}x< 3\\x>4\end{cases}}\)(vô lí)
Vậy \(x=\Phi\)
\(a,\Leftrightarrow\left(x-2\right)\left(3x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\\ b,\Leftrightarrow\left(x-2\right)^3=0\Leftrightarrow x-2=0\Leftrightarrow x=2\\ c,\Leftrightarrow\left(4x-3x-3\right)\left(4x+3x+3\right)=0\\ \Leftrightarrow\left(x-3\right)\left(7x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{3}{7}\end{matrix}\right.\\ d,\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\\ \Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\\ \Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
`A=16x^2+8x+5`
`=16x^2+8x+1+4`
`=(4x+1)^2+4>=4`
Dấu "=" xảy ra khi `4x+1=0<=>x=-1/4`
`B=x^2-x`
`=x^2-x+1/4-1/4`
`=(x-1/2)^2-1/4>=-1/4`
Dấu "=" xảy ra khi `x=1/2`
`C=a^2-2a+b^2+6b+2021`
`=a^2-2a+1+b^2+6b+9+2011`
`=(a-1)^2+(b+3)^2+2011>=2011`
Dấu "=" xảy ra khi \(\begin{cases}a=1\\b=-3\\\end{cases}\)
\(C=16x^2-8x+2024\)
\(\Rightarrow C=16x^2-8x+1+2023\)
\(\Rightarrow C=\left(4x-1\right)^2+2023\ge2023\left(\left(4x-1\right)^2\ge0\right)\)
\(\Rightarrow Min\left(C\right)=2023\)
\(D=-25x^2+50x-2023\)
\(\Rightarrow D=-\left(25x^2-50x+25\right)-1998\)
\(\Rightarrow D=-\left(5x-5\right)^2-1998\le1998\left(-\left(5x-5\right)^2\le0\right)\)
\(\Rightarrow Max\left(D\right)=1998\)
\(B=-x^2+20x+100=-\left(x^2-20x+100\right)+200=-\left(x-10\right)^2+200\le200\left(-\left(x-10\right)^2\le0\right)\)
\(\Rightarrow Max\left(B\right)=200\)
\(E=\left(2x-1\right)^2-\left(3x+2\right)\left(x-5\right)\)
\(\Rightarrow E=4x^2-4x+1-\left(3x^2-13x-10\right)\)
\(\Rightarrow E=4x^2-4x+1-3x^2+13x+10\)
\(\Rightarrow E=x^2+9x+11=x^2+9x+\dfrac{81}{4}-\dfrac{81}{4}+11\)
\(\Rightarrow E=\left(x+\dfrac{9}{2}\right)^2-\dfrac{37}{4}\ge-\dfrac{37}{4}\left(\left(x+\dfrac{9}{2}\right)^2\ge0\right)\)
\(\Rightarrow Min\left(E\right)=-\dfrac{37}{4}\)
\(F=\left(3x-5\right)^2-\left(3x+2\right)\left(4x-1\right)\)
\(\Rightarrow F=9x^2-30x+25-\left(12x^2+3x-2\right)\)
\(\Rightarrow F=-3x^2-33x+27=-3\left(x^2-10x+9\right)\)
\(\Rightarrow F=-3\left(x^2-10x+25\right)+48=-3\left(x-5\right)^2+48\le48\left(-3\left(x-5\right)^2\le0\right)\)
\(\Rightarrow Max\left(F\right)=48\)
a: \(8x\left(x-2017\right)-2x+4034=0\)
\(\Leftrightarrow\left(x-2017\right)\left(8x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2017\\x=\dfrac{1}{4}\end{matrix}\right.\)
Lời giải:
Đặt \(x^2+12=a\). Khi đó PT trở thành:
\((a+8x)(a-7x)=16x^2\)
\(\Leftrightarrow a^2+ax-56x^2=16x^2\)
\(\Leftrightarrow a^2+ax-72x^2=0\)
\(\Leftrightarrow a^2+9ax-8ax-72x^2=0\)
\(\Leftrightarrow a(a+9x)-8x(a+9x)=0\)
\(\Leftrightarrow (a+9x)(a-8x)=0\Rightarrow \left[\begin{matrix} a+9x=0\\ a-8x=0\end{matrix}\right.\)
Nếu \(a+9x=0\Leftrightarrow x^2+12+9x=0\)
\(\Leftrightarrow (x+\frac{9}{2})^2=\frac{33}{4}\Rightarrow x=\pm \frac{\sqrt{33}}{2}-\frac{9}{2}\)
Nếu \(a-8x=0\Leftrightarrow x^2+12-8x=0\)
\(\Leftrightarrow (x-6)(x-2)=0\Rightarrow \left[\begin{matrix} x=6\\ x=2\end{matrix}\right.\)
Vậy...........